Apoptotic cell death, detected ex vivo in peripheral blood lymphocytes of HIV-1 infected persons - L. F. te Velde; I. Vermes; C. Haanen; C. P. M. Reutelingsperger; C. H. H. ten Napel (Mediators of Inflammation)
In HIV-1 infection the ongoing depletion of CD4+ T-lymphocytes is believed, to a large extent, to be due to apoptosis. Until now quantitative information about in vivo apoptosis of lymphocytes in HIV-patients is scarce because of the very nature of the apoptotic process. Successful detection of apoptosis ex vivo requires the recognition of the initial phase of this process, because at a later stage the cells may not remain any longer in the circulation. We measured quantitatively the amount of early apoptotic peripheral blood lymphocytes directly ex vivo in HIV-1 infected patients using a recently described flow cytometric assay. With this method we observed in an unselected heterogenous group of twelve HIV-infected individuals a median percentage of apoptotic lymphocytes to be significantly higher than in ten healthy controls. To the best of our knowledge this is the first report of ex vivo observed increased apoptosis of peripheral blood lymphocytes in HIV-infected persons.